Analisis Kinerja dan Laporan Keuangan (Studi Kasus pada PT. Alamtri Resource Indonesia Tbk) - Hairunnisa, Sri; Rahmadi; Eskaluspita, Alit Yuniargan (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2025)
This study aims to evaluate the financial performance of PT Alamtri Resources Indonesia Tbk during the 2021-2023 period using a quantitative descriptive approach. The analysis used financial ratios, including liquidity, solvency, activity, and profitability ratios, to evaluate the company's balance sheet and income statement. The results showed fluctuations in financial performance over three years. Liquidity ratios increased in 2022 but decreased again in 2023, while solvency ratios showed a downward trend reflecting more conservative debt management. Activity ratios indicate improved efficiency in using fixed assets, but the effectiveness of total assets still needs improvement. Profitability ratios peak in 2022 but decline in 2023. These findings suggest that more efficient resource management, such as an increase in the liquidity ratio above 22% and a decrease in the solvency ratio below 3%, as well as optimization of profitability with a minimum Return on Investment (ROI) target of 2.5%, is required to maintain stability and support future growth in the company's financial performance.